Modelling Waste Management and Re-Utilization in Accommodation Sector: The Case of North Cyprus - Lafmajani, Soolmaz Azarmi (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2018)
Tourism has been acknowledged as one of the fastest growing industries in the world. However, recently tourism activities have been noted as a double-edged sword, in that it not only creates positive impacts but also causes negative impacts on the physical environment (i.e., land pollution, ecosystem degradation, air and water pollution) if not well managed. Increasing concerns about the negative impacts of tourism have led various researchers to estimate and model the role of the different tourism sectors that contribute to greenhouse gas emissions and various aspects of climate change. Northern Cyprus is a popular tourist destination in the Mediterranean region, boast of increasing number of tourists annually. Besides the massive economic benefits of the tourism industry of Northern Cyprus, there are serious environmental concerns on the basis of improper waste management. Hence, the present research focused on the statistical modelling of the waste generation rate of accommodation sectors of Northern Cyprus, management approach and the re-utilization of the generated wastes. The research herein adopted a quantitative method and the data were collected through the questionnaire. Various accommodation types based on size were sampled in Famagusta, Girne and Nicosia districts of Northern Cyprus. Specifically, the thesis examines the type of wastes generated, the quantity of wastes generated considering the nationality of the tourists, waste management practices employed by each sampled accommodation and established the relationship between these independent variables and the waste generation rate. The quantifiable wastes generated per tourism seasons were modelled by three statistical models; central composite design, artificial neural network and multiple linear regressions. The results showed that 4159.9 kg and 2063.4 kg of waste were generated during the peak and lean season from the sampled hospitality facilities, respectively. In the sampled accommodation, 36% of the waste generated originated from the kitchen waste and about one-fourth (27.3%) of the total waste is non-wet waste which consists 7% of glass, 8% of nylon, 5% of wood, 4.2% disposable plastics and 2.8% of PET bottles. 35% of the sampled accommodation sector practices landfill waste disposal, while only 14% recycled the wastes generated in their facilities. Considering the results, this thesis implied that the type of accommodation sector, the waste management practices adopted by the accommodation sector, nationality and the tourism season significantly influenced the waste generation rates. These findings are important for policymakers, environmentalist and development of sustainable green hotels. Recommendations concerning separation and re-utilization of generated wastes are suggested and future research directions are outlined. This study proposes the integration of the cost-benefit system into the waste management program of each accommodation sector to encourage hotels to manage their waste effectively. Also, the conversion of waste cooking oil into green energy (biofuel) is demonstrated and encouraged to incentivise better waste management. Keywords: tourism, environmental pollution, waste generation, reutilization, forecasting

ÖZ: Turizm, dünyadaki en hızlı büyüyen endüstrilerden biri olarak kabul edilmiştir. Bununla birlikte, son zamanlarda turizm faaliyetleri çift taraflı bir kılıç olarak görülmüştür, çünkü bu sadece olumlu etkiler yaratmaz, aynı zamanda iyi yönetilmezse fiziksel çevre üzerinde olumsuz etkilere neden olur (ör: arazi kirliliği, ekosistem bozulması, hava ve su kirliliği). Turizmin olumsuz etkileri ile ilgili artan endişeler, çeşitli araştırmacıların sera gazı emisyonlarına ve iklim değişikliğinin çeşitli yönlerine katkıda bulunan farklı turizm sektörlerinin rolünü tahmin etmelerine ve modellemelerine neden olmuştur. Kuzey Kıbrıs, Akdeniz bölgesinde popüler bir turizm beldesidir ve her yıl artan sayıda turist barındırmaktadır. Kuzey Kıbrıs turizm endüstrisinin büyük ekonomik faydalarının yanı sıra, uygun olmayan atık yönetimi temelinde ciddi çevresel kaygılar bulunmaktadır. Bu nedenle mevcut araştırma, Kuzey Kıbrıs'ın konaklama sektörlerinin atık üretim oranının istatistiksel modellenmesine, yönetim yaklaşımına ve üretilen atıkların yeniden kullanılmasına odaklanmıştır. Buradaki araştırma kantitatif bir yöntemi benimsemiş ve veriler anket yoluyla toplanmıştır. Kuzey Kıbrıs'ın Mağusa, Girne ve Lefkoşa ilçelerinde boyutuna göre çeşitli konaklama türleri örneklenmiştir. Özellikle, tez, üretilen atıkların türünü, turistlerin uyruğunu göz önüne alarak oluşturulan atıkların miktarını, her bir örnekdeki konaklama tarafından kullanılan atık yönetimi uygulamalarını incelemekte ve bu bağımsız değişkenler ile atık üretim oranı arasındaki ilişkiyi ortaya koymaktadır. Turizm mevsimlerine göre üretilen ölçülebilir atıklar üç istatistiksel modelle modellenmiştir; merkezi kompozit tasarım, yapay sinir ağı ve çoklu doğrusal regresyon. Sonuçlar, örneklenmiş konukseverlik tesislerinden en yüksek ve zayıf mevsim boyunca sırasıyla 4159.9 kg ve 2063.4 kg atık üretildiğini göstermiştir. Örneklenen konutta, üretilen atığın %36'sı mutfak atığından kaynaklanmakta ve toplam atığın yaklaşık dörtte biri (% 27.3) ıslak atık değildir, %7'si cam, %8'i naylon, %5'i odun, %4.2'sini tek kullanımlık plastikler ve %2,8 PET şişeler'den oluşmaktadır. Örneklenen konaklama sektörünün %35'i çöp atıklarının bertarafını gerçekleştirirken, sadece %14'ü tesislerinde üretilen atıkları geri dönüştürmektedir. Sonuçlar dikkate alındığında, bu tez, konaklama sektörünün türünün, konaklama sektörünün benimsediği atık yönetimi uygulamalarının, uyruk ve turizm mevsiminin atık üretim oranlarını önemli ölçüde etkilediğini göstermektedir. Bu bulgular politika yapıcılar, çevreci ve sürdürülebilir yeşil otellerin gelişimi için önemlidir. Üretilen atıkların ayrıştırılması ve yeniden kullanımı ile ilgili öneriler önerilmekte ve gelecekteki araştırma yönleri özetlenmektedir. Bu çalışma, otellerin atıklarını etkili bir şekilde yönetmelerini teşvik etmek için her bir konaklama sektörünün atık yönetim programına maliyet-fayda sisteminin entegrasyonunu önermektedir. Ayrıca, atık pişirme yağının yeşil enerjiye dönüştürülmesi (biyoyakıt) daha iyi atık yönetimini teşvik etmenin ıspatıdır. Anahtar Kelimeler: turizm, çevre kirliliği, atık üretimi, yeniden kullanım, öngörme
Doctor of Philosophy in Tourism Management. Thesis (Ph.D.)--Eastern Mediterranean University, Faculty of Tourism, 2018. Co-Supervisor: Assoc. Prof. Dr. Akeem Oladipo, Supervisor: Prof. Dr. Habib Alipour.
Keywords: Tourism; Hazardous waste management industry--Waste Management--Green Tourism--Cyprus (Turkish Republic of Northern Cyprus, 1983-); Tourism; environmental pollution; waste generation; reutilization; forecasting